If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = -3x + 6 Reorder the terms: 2 + 2x = -3x + 6 Reorder the terms: 2 + 2x = 6 + -3x Solving 2 + 2x = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + 2x + 3x = 6 + -3x + 3x Combine like terms: 2x + 3x = 5x 2 + 5x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 2 + 5x = 6 + 0 2 + 5x = 6 Add '-2' to each side of the equation. 2 + -2 + 5x = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 6 + -2 5x = 6 + -2 Combine like terms: 6 + -2 = 4 5x = 4 Divide each side by '5'. x = 0.8 Simplifying x = 0.8
| 2x+2=4x+-6 | | cos(7x+ln(5x))=0 | | lx^2+3x+1l=1 | | 9-3x+2=10-3x | | 20+0.07(x-20)=0.06x | | 3u^2+3v^2-6uv+20u-20v+12=0 | | 1x-3y=14 | | Xy-4x+10=0 | | 9x+11=5x+1 | | 20+0.07x=0.06x | | x+9+2x=30 | | 11+2a=14 | | 3p=60+8p | | .2(x+100)=10 | | (-12)+6/2= | | 59-6x=3x+16 | | 20x+50b=320 | | -3x-y=17 | | 120+12x=545 | | 9x-2-4x-13=30 | | 4x^2-100x+625=0 | | x^2+20x+225=0 | | 4x-1=15x+1 | | 7x-6=58 | | 6x+29=Y | | x-16=-35 | | X+(3+X)=43 | | 150=3x^2 | | 2x+2=-4x+56 | | 20x+50b=8(40) | | 6(2x-1)-12=7+12(1x-1) | | 8+5x=37 |